Alternative splicing regulation and its therapeutic potential in bladder cancer - Li, Lina; Jin, Ting; Hu, Liang; Ding, Jin (Frontiers in Oncology, 2024)
Bladder cancer is one of the leading causes of mortality globally. The development of bladder cancer is closely associated with alternative splicing, which regulates human gene expression and enhances the diversity of functional proteins. Alternative splicing is a distinctive feature of bladder cancer, and as such, it may hold promise as a therapeutic target. This review aims to comprehensively discuss the current knowledge of alternative splicing in the context of bladder cancer. We review the process of alternative splicing and its regulation in bladder cancer. Moreover, we emphasize the significance of abnormal alternative splicing and splicing factor irregularities during bladder cancer progression. Finally, we explore the impact of alternative splicing on bladder cancer drug resistance and the potential of alternative splicing as a therapeutic target.